LZ compression of static linked list tries - Ristov, Strahil (Array, 1997)
A variant of LZ procedure for compressing static trie structures is investigated for different types of natural language data. A compressed trie is produced from the set of 40,000 bilingual dictionary entries and the results are compared to previous results for a set of 750,000 different word forms. A possible use of a sliding window in LZ procedure for linearization of algorithm execution time is investigated. The results show considerable application potential.